We can Recite it in Chorus Now!: An Interactionist Approach to the Teacher–Student Relationship and Teachers' Relational Competence. Issue 1 (2nd January 2017) - Aspelin, Jonas
Abstract: A growing body of international research demonstrates that supportive teacher–student relationships have multiple positive educational effects. In Scandinavia, the concept of relational competence is increasingly used to define the teacher's ability to develop 'good' relationships. The overall purpose of this article is to contribute to the field by adopting an interactionist perspective. Drawing chiefly on T. Shibutani, but also on G.H. Mead and T. Scheff, the article aims to: (i) examine how the teacher–student relationship is constructed through nonverbal communication and (ii) discuss the implications regarding teachers' relational competence in situated teaching. A detailed transcript of a classroom episode is interpreted and analysed using Shibutani's concepts. The analysis reveals two parallel relational matrices, one 'conventional' and the other 'interpersonal'. In the concluding section, it is argued that the relationship between the two matrices plays an important role in understanding teachers' relational competence: the relationally competent teacher takes responsibility for his/her own actions, both as an educator in a conventional system and as a fellow being in an interpersonal system. Expressed differently, relational incompetence means overemphasizing one system at the expense of the other.